A Compact Building Block With Two Shared-Aperture Antennas for Eight-Antenna MIMO Array in Metal-Rimmed Smartphone - Ren, Aidi; Liu, Ying; Sim, Chow-Yen-Desmond (IEEE transactions on antennas and propagation, 2019)
In this paper, a compact building block composed of a slot antenna and a loop antenna is proposed. The slot antenna and the loop antenna share a rectangular clearance, which improves the compactness of the building block effectively. Although the slot and the loop have overlapped completely, the proposed building block exhibits good isolation (better than 19 dB) without any external decoupling structure. Four such building blocks are used to implement a compact eight-port multiple-input multiple-output (MIMO) array operating at 3.5 GHz band (3.4-3.6 GHz) for fifth-generation (5G) metal-rimmed smartphone applications. The proposed eight-antenna MIMO array exhibits good isolation of better than 16 dB across the whole operating band. The measured efficiencies of the proposed MIMO array were between 59% and 73%, and its corresponding measured envelope correlation coefficients (ECCs) were better than 0.05. Furthermore, the calculated channel capacity of the proposed MIMO array with 20 dB signal-to-noise ratio (SNR) was about 38.2-39.8 bps/Hz across the desired bands (3.4-3.6 GHz). The measured results confirm that the proposed MIMO array is a good candidate for 5G terminals.